Ensino de artes visuais e artesania: experiências, confluências e derivas - Peixe, Rita Inês Petrykowski; Hernández-Hernández, Fernando; Prieto Villanueva, Jesús-Ángel; Canônica, Rosangela (Revista GEARTE, 2020)
Apresentação